Dynamic Stability and Interlaminar Stress Analysis of Cylindrical Shells Subjected to Elevated Thermal Field. (2016) - Das, R.R.; Singla, A.
Abstract: Three-dimensional thermo-mechanical stress analyses of cylindrical shell structures made with laminated Fibre Reinforced Polymer (FRP) composites have been carried out. Brick 8-node 185 layered solid elements have been used in the present finite element simulation. Due to curved geometry and interaction of different coupling modes at the ply-interfaces, stress concentration effects have been realized throughout the domain of the laminated shell structure. Appropriate finite element mesh size obtained through convergence study has been adopted to capture these stress concentration effects. Thermal field induced out-of-plane interlaminar stresses (σrr, τθr, τzr ) responsible for delamination damage initiations have been analyzed in details. Effect of different stacking sequences on thermo-mechanical dynamic stability of shell structures has also been studied. It has been observed that, structural dynamics of composite shell structures get significantly affected under elevated thermal field.